Selenite elimination via zero-valent iron modified biochar synthesized from tobacco straw and copper slag: Mechanisms and agro-industrial practicality - Luo, Qiong; Chen, Dingxiang; Cui, Ting; Duan, Ran; Wen, Yi; Deng, Fang; Li, Lifang; Wang, Huabin; Zhang, Yong; Xu, Rui (Frontiers in Bioengineering and Biotechnology, 2022)
Cost-effectively improving the performance of biochar is essential for its large-scale practical application. In this work, the agro-industrial by-products copper slag and tobacco straw were employed for the preparation of modified biochar (CSBC). The obtained CSBC exhibited satisfactory capacity on Se(IV) immobilization of 190.53 mg/g, with surface interactions determined by the monolayer and mainly chemisorption. The removal mechanisms included chemical reduction, electrostatic attraction, co-precipitation, and formation of complexations. Interestingly, the existence of Cu2Se structure after adsorption indicated the involvement of Cu species within Se(IV) elimination. Moreover, the industrial agricultural practicality of CSBC was evaluated by regeneration tests, economic assessment, and pot experiments. The results demonstrate that iron species-modified biochar prepared from two agro-industrial by-products is a promising and feasible candidate for selenite removal from wastewater.